An investigation of the maintenance programs applied on Masjid in Selangor / Zakaria Ibrahim - Ibrahim, Zakaria (2014)
The word masjid is from the Arabic, which translates literally as "place of prostrations", and the building is a house of worship for Muslims. The masjid is also" the outward and visible symbol of Islam". (Powell, 2002). Maintenance is work that is carried out to preserve an asset (such as a roof, structure, or other component),in order to enable its continued use and function, above a minimum acceptable level of performance, over its design service life, without unforeseen renewal or major repair activities. A good mosque maintenance also important thing to provide the best condition in or out a masjid, that make people felt comfortable to worship Allah. The application of maintenance program in a building is not too comprehensive to all buildings, but for the building like Masjid is an important thing to show it as a symbol of Islam. The aim of this study is to investigate the maintenance programs applied for masjid in Selangor. The main objective of this research is to study the application of maintenance programs applied for masjid in Selangor. Furthermore, the objective of this study also to identify the problems and issues in the maintenance of the masjid in Selangor and to propose are commendation of improvement in the current maintenance program of masjids in Selangor. The finding of this research shows the most of maintenance in the masjid is unplanned maintenance, however, for masjid like Masjid Sultan Salahuddin Abdul Aziz Shah which is state masjid and largest in south Asia is applied plan maintenance. A masjid will continue to be a valuable asset only if it is properly operated and maintained. It requires maintenance to keep up its structural integrity as well as its aesthetic appearance both inside and outside.